Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
1. x = [tex]\frac{a}{y}[/tex]
xy = a
y = [tex]\frac{a}{x}[/tex]
2. 3+x-d = e
x-d = e - 3
x = d+e-3
3. axy = z
ax = [tex]\frac{z}{y}[/tex]
a = [tex]\frac{z}{y}[/tex] : x
4. [tex]\frac{x-1}{3}[/tex] = k
x-1 = 3k
x = 3k + 1
5. 2P = (a+b)h
[tex]\frac{2P}{h}[/tex] - a = b
6. x = [tex]\frac{a}{4}[/tex] +2
4x = a + 8
4x - 8 = a
Odpowiedź:
1.
x =[tex]\frac{a}{y}[/tex]/*y
[tex]xy=a[/tex]/:x
y=[tex]\frac{a}{x}[/tex]
2.
3 + x – d =e
x=e+d-3
3.
axy = z /:xy
[tex]a=\frac{z}{xy}[/tex]
4.
[tex]\frac{x-1}{3}=k[/tex]/*3
x-1=3k
x=3k+1
5.
P = [tex]\frac{(a+b)*h}{2}[/tex]/*2
2P=(a+b)*h
2P=ah+bh
2P-ah=bh/:h
b=[tex]\frac{2P-ah}{h}[/tex]
6.
x = [tex]\frac{1}{4}[/tex] a + 2
x-2=¹/₄a/*4
4(x-2)=a
a=4x-8
Szczegółowe wyjaśnienie: